Factors that cause head injuries in pedestrian-scooter crashes - Ang, Alan Teck Ming (Nanyang Technological University, 2020)
The increasing number of cases of pedestrian-scooter collision on Singapore footpaths in the past few years have led to the purpose of this study to learn more about the occurrence of such accidents. Since the allowance of PMDs in Singapore, we have seen a rising usage of e-scooters by Singaporeans to commute from one place to another. The laws and policies for the usage of PMD allow for the users to ride on footpaths. However, accommodating both walking pedestrians and the PMDs make the footpath more congested and increases the chances of collision between the two user groups. The collision causes the pedestrian to fall over and this may result in the pedestrian to hit his head onto the ground. The purpose of this study is to study the impact between the head and the footpath after a fall and the factors that cause head injuries. This study looks at the behavioural response of a person reacting to a fall as well as looking into past medical studies regarding head injuries. The objectives of the experiments conducted in this study is to find out how impact velocities to the head is determined by dropping heights and how these factors relate to the degree of head injuries using calculations based on professional medical terminologies such as the head injury criterion (HIC) and abbreviated injury scale (AIS).